EFFECTIVENESS OF CTL-BASED ELECTRONIC MODULE DEVELOPMENT FOR WRITING LEARNING HIGH SCHOOL STUDENTS - Afnita, Afnita (TELL - US JOURNAL, 2022)
This study aimed to test the effectiveness of developing a CTL-based electronic module in learning to write expository texts for class X SMA Negeri 12 Padang students. In testing the effectiveness of this module, the development model used is the Four-D (4D) model. Testing the effectiveness of the electronic module was obtained from two sources, namely observations of activities during the learning process and the results of the performance test of writing exposition texts. The research findings indicate that the results of the analysis of student activities in the learning process using electronic modules conducted through observation sheets are categorized as very active. This can be seen from the average value of the percentage of student activity as a whole of 89.18 with a very active category. Judging from the results of student performance tests, the use of this CTL-based electronic module is also very effective. This can be proven by the average score of students in writing exposition texts is 87. Based on the research findings, it can be concluded that the CTL-based electronic module developed is very effective in learning to write expository texts and can improve student learning outcomes in class X SMA Negeri 12 Padang.